Are immigrants paid less for education? - Anastassova, Lubomira (Luxembourg, 2010)
"This paper is on measuring the gap in returns to education between foreign-born and native workers in France, Germany, and Austria and investigates the extent to which this gap can be explained by a mis-match between the actual and the years of schooling typical for a given occupation. The return to usual years of schooling across different occupations is found to be higher than that for actual years of education. In the case of correctly matched workers who have the `typical? education in a certain occupation, there is no additional reward in earnings for natives compared to foreign workers. Immigrants, however, have significantly lower wage returns in being over-educated than natives but are penalized less for being under-educated."